Lactoferrin binds to porins OmpF and OmpC in Escherichia coli. - Erdei, J (1994)
Lactoferrin (Lf) is an iron-binding antimicrobial protein present in milk and on mucosal surfaces, with a suggested role in preimmune host defense. Certain strains of Escherichia coli (bacterial whole cells) demonstrate specific interaction with 125I-labeled Lf. A band with a mass of approximately 37 kDa, which was reactive with horseradish peroxidase-labeled Lf, was identified in the boiled cell envelope and outer membrane preparations of an Lf-binding E. coli strain, E34663, and a non-Lf-binding strain, HH45, by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting (immunoblotting). Such a band was not detected in the unboiled native cell envelope and outer membrane preparations. The molecular mass and the property of heat modifiability suggested that the Lf-binding proteins were porins. The native trimeric form of porin OmpF isolated from strain B6 and its dissociated monomeric form both reacted with horseradish peroxidase-labeled Lf and with monoclonal antibodies specific for OmpF. Furthermore, by using E. coli constructs with defined porin phenotypes, OmpF and OmpC were identified as the Lf-binding proteins by urea-SDS-PAGE and Western blotting and by 125I-Lf binding studies with intact bacteria. These data establish that Lf binds to porins, a class of well-conserved molecules common in E. coli and many other gram-negative bacteria. However, in certain strains of E. coli these pore-forming proteins are shielded from Lf interaction.